The Tradition of Tulak-Manulak (Sharing and Receiving) of Rice As An Effort for Compensation (Fidyah) for Prayer and Fasting - Ali Sati (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Specifically regarding to compensation for eliminating the obligation to perform prayers, it is not explicitly regulated, either in al-Qur'ânul Karîm or the Hadith of the Prophet SAW as two sources of law that must be a guide in living this life. The method used in this study is qualitative-descriptive. Meanwhile, the approaches are phenomenology, ethnography and case studies. The research results, it can be seen that there is certainly no problem with fasting fidyah, because the rules are very clear. This is different from fidyah prayer which is not regulated, either in the Koran or the hadith of the Prophet SAW. In fact, when a prayer is neglected, it must be replaced with the same prayer even if it is outside the time. When this was stated, those who were considered as executors who were directly involved in the implementation of fidyah payments (conventions) were only based on the hadith (mauqûf) of Ibn 'Abbas ra. which contradicts the text (matn) of the hadith of 'Imrân bin Hushayn, so that the hadith is considered weak (dha'îf). When this is confirmed say; knew about it, but they said that the fidyah payment was carried out as a hope (rajâ, tafâ'ul, sinta-sinta); May Allah be pleased with His mercy and blessings.